2018
DOI: 10.1002/lary.27419
|View full text |Cite
|
Sign up to set email alerts
|

Kids Nowadays Hear Better Than We Did: Declining Prevalence of Hearing Loss in US Youth, 1966–2010

Abstract: Objectives/Hypothesis To investigate factors associated with hearing impairment (HI) in adolescent youths during the period 1966–2010. Study Design Cross‐sectional analyses of US sociodemographic, health, and audiometric data spanning 5 decades. Methods Subjects were youths aged 12 to 17 years who participated in the National Health Examination Survey (NHES Cycle 3, 1966–1970; n = 6,768) and youths aged 12 to 19 years in the Third National Health and Nutrition Examination Survey (NHANES III, 1988–1994; n = 3,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…However, outcroppings of socioacusis and nosoacusis are observable as changes in cross-sectional trends over time. For example, improvements in the hearing sensitivity of the U.S. population have been observed across all age groups during the last 60 years (Hoffman et al 2010(Hoffman et al , 2012(Hoffman et al , 2017(Hoffman et al , 2019, with significant improvements over the brief period between 1999-2004 and 2011-2012 (Hoffman et al 2017). Such improvements are attributable to changes in socioacusic and nosoacusic exposure profiles rather than changes in the inexorable effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcroppings of socioacusis and nosoacusis are observable as changes in cross-sectional trends over time. For example, improvements in the hearing sensitivity of the U.S. population have been observed across all age groups during the last 60 years (Hoffman et al 2010(Hoffman et al , 2012(Hoffman et al , 2017(Hoffman et al , 2019, with significant improvements over the brief period between 1999-2004 and 2011-2012 (Hoffman et al 2017). Such improvements are attributable to changes in socioacusic and nosoacusic exposure profiles rather than changes in the inexorable effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…OM leads to conductive hearing loss (vs sensorineural) and is unquestionably a principal risk factor for childhood hearing loss; recent studies have also demonstrated associations with adult sensorineural hearing loss . To gain perspective and appreciation for the aetiology of childhood hearing loss, a fuller examination of established factors may be useful …”
mentioning
confidence: 99%
“…These children were identified at ages 3, 4, or 5 years based on pure‐tone average thresholds across 500, 1000, and 2000 Hz in the moderate (40‐60 dB), severe (61‐90 dB), or profound (>90 dB) hearing loss range. The prevalence of moderate‐to‐worse hearing impairment among preschool‐aged children in The Netherlands was not provided; however, it is likely to be 1‐2 per 1000 children …”
mentioning
confidence: 99%
See 2 more Smart Citations